Analisis Finansial Pembesaran Ikan Bandeng (Chanos chanos) pada Tambak Tradisional dengan Sistem Monokultur dan Polikultur di Kecamatan Mulyorejo, Surabaya, Jawa Timur [ Financial Analysis of Fish Enlargement Milkfish (Chanos chanos) in Pond with Traditional Farming and Monoculture Polyculture System in Mulyorejo, Surabaya, East Java] - Moch. Amin Alamsjah; Kustiawan Tri Pursetyo; Asmaul Huniyah (Faculty of Fisheries and Marine Universitas Airlangga, 2015)
Abstract Fishing is one of the economic sectors that have potential and an important role for the Indonesian economy. The fisheries sector also have contributed to the national development can be seen from its function as a provider of raw materials driving agro-industries, increase the supply of foreign exchange through the export of fishery products, providers of employment opportunities, increase the income of fishermen or fish farmers and regional development, as well as increasing the sustainability of fishery resources and the environment. The method used in this research is descriptive method. The process of data collection was conducted by questionnaire survey method with existing guidelines. Survey methods not only to create a description of a situation, but also to explain the relationship between the various variables studied. Data collection can use a questionnaire or survey questionnaires, interviews or observation in accordance with the needs of researchers (Moleong, 2009). This study aims to determine the potential for cultivation of fish rearing milkfish (Chanos C.) were performed on traditional pond polyculture and monoculture systems by farmers in districts Mulyorejo. Potential cultivation can be known through a financial analysis that determines a feasible endeavor or not to do business development. Results from this study indicate that milkfish fish rearing business conducted in the region, including in businesses that are not feasible, because the percentage of farmers who obtained a profit of 20% and the loss of 80% .. The average value of B / C Ratio obtained by farmers ie -0.17, the average value obtained by farmers Payback Period at 0 and the average value obtained Return on Investment farmers amounted to -22%. The third data indicate that milkfish fish rearing business is done in traditional ponds in the districts Mulyorejo not in accordance with the standards of good business and profitable .